Infiltrating healthcare how marketing works underground to influence nurses - Grundy, Quinn, 1986- (Johns Hopkins University Press, 2018)
It was once common for pharmaceutical companies and medical device makers to treat doctors to lavish vacations or give them new cars; companies would do virtually anything to buy influence so that their medications or devices would be used in a doctor's office or hospital. But with growing public scrutiny of kickbacks to doctors, the huge giveaways have disappeared. In Infiltrating Healthcare, Quinn Grundy shows that sales representatives are working instead behind the scenes. It is to nurses that these companies now market. Nurses, Grundy argues, are the perfect target for sales reps: their work is largely invisible and frequently undervalued, yet they wield a great deal of influence over treatment and purchasing decisions. Furthermore, there are no legal restrictions on marketing to most nurses. Grundy describes how, under the guise of education or product support, and through gifts and free samples, sales representatives influence nurses in the course of day-to-day clinical practice. Grundy argues that the very presence of sales reps in operating rooms, purchasing committee meetings, and patient care units blurs the boundaries between patient care and medical sales. Helpfully, she also describes ways that nurses can be aware of (and resistant to) their influence. Infiltrating Healthcare is a call to action to protect the clinical spaces where we are at our most vulnerable--and the decisions that take place there--from the pursuit of profit at any cost. This is a timely book that shines a light on a practice that often goes unseen, and which has tangible implications for healthcare policy and practice. -- Provided by publisher.